Investigation of Anti-Cancer Potency of Sarsasapogenin: In vitro and In silico Insights against MDR Cell Line-KB-Chr-8-5 - Alhakami, Fatemah Abdulaziz; Mawkili, Wedad; Dayel, Faten F Bin; Mawkili, Abdullah; Albaqami, Amirah; Albogamy, Norah T.S; Narasimhamoorthi, Shilpa Perumal (Indian Journal of Pharmaceutical Education and Research)
Objectives: Cancer recurrence is a major global concern, contributing to the rising mortality rates in the most common types of cancer. To overcome these incidents, highly qualified herbal medicines are more targetable, thus this investigation demonstrates the treatment of a steroidal bioactive compound-Sarsasapogenin (SAR). Materials and Methods: To achieve the goal, Anti-oxidant capacity of SAR was studied by DPPH and ABTS assay. Cytotoxicity assessment was performed as first line confirmation about its anti-cancer potency through Tetrazolium assay and Trypan blue assay. Oxidative stress balance was examined by enzymatic assays (NO, LPO, SOD and CAT). Further, apoptosis was confirmed by fluorescence staining (DAPI, DCHFDA) and cell cycle analysis. In silico work was also performed to detect the interaction between ABCC1 protein and SAR using molecular docking studies. Results: Anti-oxidant assay confirmed SAR is a potent radical scavenger with cytotoxic potential at IC50 value of 600 μg/mL. Enzymatic assays, fluorescence staining and flow cytometry proved its anti-proliferative property which showed elevation of stress related enzymes and reversal in anti-oxidant enzymes. Nuclear damage was observed in DAPI, enormous free electron production in DCFDA assays and cell cycle arrest at late cell cycle phase respectively. Conclusion: In the point of conclusion, investigation performed with SAR against KB-ChR-8-5 showed remarkable anti-proliferative activity which paves the way for application of SAR as futuristic drug candidate especially in Multi Drug Resistant (MDR) cancer.
Keywords: Sarsasapogenin; Multi drug resistant; KB-ChR-8-5; Cancer recurrence; ABCC1; MRP 1.